Time–temperature superposition in the grain and grain boundary response regime of A2HoRuO6 (A = Ba, Sr, Ca) double perovskite ceramics: a conductivity spectroscopic analysis. Issue 69 (11th September 2017) - Halder, Saswata; Dutta, Alo; Sinha, T. P.
Abstract : The realisation of a universal scaling parameter accounting for the time–temperature superposition principle in different electroactive microstructural domains seems improbable. Abstract : The pursuit for a universal scaling factor to satisfy the time–temperature superposition principle for grain and grain boundary responses has been explored in the ac conductivity domain for polycrystalline double perovskite oxides A2 HoRuO6 (AHR; A = Ba, Sr, Ca). The samples show different structural phases, from cubic to monoclinic, with decreasing ionic radii. The degree of distortion in the materials is correlated to the strength of the bonding through the bond valence sum (BVS) formalism. The conductivity spectra for all of the samples obey the power law variation. The contribution of different microstructural domains to the conduction process is established. Thermal variation of the dc resistivity points towards a gradual crossover from nearest neighbour to variable range hopping. The activation energies obtained from the dc conductivity, hopping frequency and relaxation frequency show close correlation between the conduction and relaxation mechanisms. The scaled conductivity curves for AHR display the presence of two different conduction processes with dissimilar activation energies in the grain boundary and the grain response regimes. It is thus concluded that a single scaling parameter is insufficient to satisfy the time temperature superposition principle universally when two different thermally activated regions are present simultaneously in the materials.